CHLORITE GEOTHERMOMETRY AND PHYSICOCHEMICAL CONDITIONS OF GOLD MINERALIZATION IN THE PALEOPROTEROZOIC CAXIAS DEPOSIT, SÃO LUÍS CRATON, NORTHERN BRAZIL - Klein, E. L.; Koppe, J. C. (Geochimica Brasiliensis, 2011)